Émile Durkheim and the So-Called Hobbes’ Problem of Order: What Lies Beneath the "First Sociological Myth" - Maršálek, Jan (Teorie vědy / Theory of Science, 2009)
This paper deals with the relationship between Emile Durkheim’s sociology and the contractualist tradition of political philosophy, represented here principally by Thomas Hobbes. Its aim is to show that Giddens’s strict rejection of Parsons’s claim according to which Durkheim has reopened in his work the “Hobbes’s problem of order”, should not be accepted as such, because it’s radicality hides that what is the value in Parsons’s thesis. As we argue, Parsons has the merit of noticing that Hobbes and Spencer, who – in respect of their social philosophies – are usually seen as opposed, appear to be close to each other when they are considered by Durkheim as to the conception of the society their philosophies yield. Yet Durkheim’s criticism of their individualistic conception of society results in a critique of their theories of the state. It is then proposed that Durkheim’s sociology is an endeavour to conceive the society independently of the state, and thus, inversely, to emancipate the state from the society, so that it can be entrusted with a different function other than the guarantor of the social order.